Microbiological Quality of Drinking Water and Beverages in Karachi, Pakistan: Microbiological Quality of Drinking Water (Biological Sciences - PJSIR, 2010)
Microbiological assay of 780 water samples and 1220 beverage samples (412 branded and 808 unbranded), collected from 490 different schools, both government (98 schools) and private (392 schools), situated in different areas of the city of Karachi, was conducted for bacterial heterotrophic plate count, total coliforms, faecal coliforms, E. coli, faecal streptococci, Pseudomonas and Salmonella species. The counts ranged from 0 to 2.5 ´ 105 cfu/mL and from 0 to 106 cfu/mL in water and beverage samples, respectively. About 36% of water samples and 48% of unbranded beverage samples were contaminated with the indicator and the pathogenic bacteria; all the branded beverage samples were found fit for human consumption from microbiological viewpoint.